Association of single-nucleotide polymorphisms in RHOB and TXNDC3 with knee osteoarthritis susceptibility: two case-control studies in East Asian populations and a meta-analysis - Shi, Dongquan (BioMed Central, 2008)
INTRODUCTION: Conflicting findings on the association of single nucleotide polymorphisms (SNPs) in RHOB and TXNDC3 with susceptibility to knee osteoarthritis (OA) have been reported in European Caucasians. To examine the associations of these SNPs with OA in East Asian populations and to evaluate their global significance, we conducted two case-control studies in 955 Chinese and 750 Japanese patients. METHODS: We genotyped the previously implicated SNPs rs585017 (in RHOB) and rs4720262 (in TXNDC3) in patients with primary symptomatic knee OA with radiographic confirmation and in matched control individuals, and analyzed their associations. We further conducted a meta-analysis of the study findings together with those of previously reported European studies using the DerSimonian-Laird procedure. RESULTS: A significant association of RHOB with knee OA was observed in male Chinese patients (P = 0.02). No significant associations were found for RHOB in any other comparisons in the East Asian populations. The association of TXNDC3 was replicated in Chinese female (P = 0.04) and Japanese (P = 0.03) patients, although none of these associations persisted after Bonferroni correction. Significant association (P = 0.02 for the allelic frequency) with nonsignificant heterogeneity was found in the East Asian replication study. No significant association was found in any comparison in the meta-analysis for all studies. CONCLUSION: Our study replicates the association, previously reported in European Caucasians, of TXNDC3 with knee OA susceptibility in an East Asian population.